(untitled) (The Agriculturists, 2018)
The present study attempted to estimate the profitability, domestic resource cost (DRC) and problems and prospects of onion production in the study areas. Both primary and secondary data were used in this study. Sample survey was carried out in two selected areas under Kushtia and Jhenaidah districts. A total of 110 onion producers were selected randomly of which 70 producers were from Kushtia and the remaining 40 producers were from Jhenaidah. The study showed that, on an average, total costs of onion production per hectare were about Tk. 150,097 and 116,831 in Kushtia and Jhenaidah district, respectively. The benefit cost ratios (BCR) of onion production were 2.02 and 1.83 in Kushtia and Jhenaidah district, respectively. The results of profitability and BCR show that onion is a profitable crop in Bangladesh. The domestic resource costs (DRC) were 0.47 in Kushtia and 0.52 in Jhenaidah, which indicate that Bangladesh has comparative advantage in onion production. The coefficients of the production function show that farm area, irrigation, pesticides, seeds, chemical fertilizers (TSP) and labor were statistically significant affecting factors of onion production and it shows constant returns to scale. The onion producers faced some production, technological and marketing related problems in the study areas. The government should therefore, take necessary policies for further development of onion production in Bangladesh. The Agriculturists 2017; 15(2) 66-78